A inclusão escolar pelo olhar de participantes da ReAD: narrativas de professoras e licenciandas - Almeida, Amanda Carolina Marmo de (Universidade Federal de São Carlos, 2023)
Nowadays, school inclusion represents a significant advance for Brazil, the result of efforts and important achievements not only in the educational context but also in social, political, and cultural. The outlined master's research had as the object of analysis written narratives of teachers and undergraduate students, raised through an online Extension Activity called ReAD (“Rede de Aprendizagem e Desenvolvimento da Docência” in Brazilian Portuguese, which means Teaching Learning and Development Network) in the Virtual Learning Environment (AVA Moodle) of UFSCar. The online Extension Activity had the following issue “What do teachers and undergraduate students participating in the Teaching Learning and Development Network (ReAD) reveal about the development of Special Education from the perspective of school inclusion?”, the objective was to identify and characterize the representations, challenges, ways of facing, and possibilities of pedagogical practices in the narratives of ReAD participants regarding school inclusion. The study was developed from a qualitative approach and had the participation of three teachers from the regular classroom, three teachers from the AEE (“Apoio Educacional Especializado” in Brazilian Portuguese, which means Specialized Educational Support), and three undergraduate students in Pedagogy at the Federal University of São Carlos (UFSCar), in the distance modality. As instruments for data collection, forms, posts in forums, analysis of a teaching case, and experience reports were used. After finishing the Extension Activity, data were tabulated, dividing them into categories and subcategories, highlighting relevant aspects, and thus building the categories of analysis. Three categories of analysis were established: Representations revealed by the ReAD participants, with the subcategories being teacher, school inclusion, and representations about the teaching and learning process; Challenges and ways of facing them revealed by the ReAD participants, with the subcategories: challenges to the teaching and learning process and teaching work conditions; Possibilities of pedagogical practices revealed by the ReAD participants, with the subcategories: possibilities of pedagogical practices for the teaching and learning process and teacher training. The data obtained show that school inclusion is a complex process for teachers and undergraduate students and involves not only their representations about teaching and the professional development of teachers but also the challenges of practice and training gaps. In summary, the research participants understand that PAEE (“Público-Alvo da Educação Especial, which means Target-audience of Special Education) students should be in regular classrooms in regular schools, but they highlight that this involves teacher training, building support networks, the partnership between school and family, elimination of barriers (attitudinal, architectural and technological), the guarantee of rights such as AEE, collaborative work and also resources, strategies and curricular adjustments that meet the specificities, needs and abilities of PAEE students. In addition, precarious infrastructure, high workload, lack of support from the management team, the high number of students in the classroom, and low salaries, were some of the working conditions denounced by teachers and undergraduates. In this way, good working conditions and appreciation of the teaching career proved to be essential for school inclusion to take place. Despite the challenges, the research participants indicated their ways of facing and presented possibilities for pedagogical practices related to the teaching and learning process and teacher training, showing that they are in motion in the search for school inclusion in the PAEE. In conclusion with the results, the ReAD as an online learning network favored intergenerational dialogue and also provided moments of training and reflection for teachers and undergraduates, contributing to the process of school inclusion and, consequently, to the accomplishment of a school for all, inclusive and democratic.
School inclusion from the perspective of participants in ReAD: narratives of teachers and undergraduate students
Keywords: Inclusão escolar; Educação Especial; Formação de Professores; ReAD; School inclusion; Special Education; Teachers Education; ReAD; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO